A relationship between research skills and autonomous learning among postgraduate students - Md Azmi, Nur Afiqah; Daud, Nadwah (Zes Rokman Resources, 2019)
Knowledge of research methodology and the skill of applying it in research are two important things required by postgraduate student in producing a good research. A postgraduate student who is equipped with research skill or knowledge of research methodology and able to apply it while conducting research therefore, should be autonomous in research writing. The idea of autonomy raises important highlight that need to be explored, particularly in terms of students’ taking responsibilities for learning, while this recent research focuses on the practice of autonomy among postgraduate students in conducting research. This paper looks into whether research skills or knowledge of research method is significantly related to autonomy in learning among postgraduate students with abilities to plan for research writing and monitor the strategies used, evaluate its progress and maintain the motivation of research writing. To address this problem, this study is carried out to investigate the relationship between research method skill and autonomous learning among 125 postgraduate students from the Department of Arabic Language and Literature (DALL) at the International Islamic University Malaysia (IIUM), by using Pearson Correlation Coefficient. The result shows that there is a significant relationship between these two variables, hence the hypothesis of this study is accepted.